The Forensic Analysis of Gunshot Residue Techniques and Applications (Medical Forum Monthly, 2023)
Objective: To determine frequency of thrombocytosis and elevated C- reactive protein levels in different stages of esophageal carcinoma in a tertiary care hospital of Karachi.Study Design: Descriptive, Cross –Sectional studyPlace and Duration of Study: This study was conducted at the Surgical unit 05, Civil Hospital Karachi from 27 February 2018 to 26 February 2019.Materials and Methods: A total of 97 patients with esophageal carcinoma on histopathology were included in the study. Diagnosed cancer patients were further assessed for stage of tumor via radiological investigations like Computed tomography scan Chest+ Abdomen with contrast and Endoscopic ultrasound. Platelet counts and C- Reactive protein levels was assessed in different stages of esophageal carcinoma using Tumor Nodal Metastasis staging system for esophageal cancer.Results: The average age was 48.88±10.13 years. Frequency of elevated C- reactive protein and platelet count in esophageal carcinoma were observed in 73(75.26%) and 31(31.96%) while both were elevated in 29(29.9%) cases. Elevated CRP was significantly high in stage 3 and 4 esophageal carcinomas (p=0.0005) while and platelet count (> 400,000/Liter called thrombocytosis) were not statistically significant among stages of esophageal carcinoma (p=0.878).Conclusion: Our findings confirmed that CRP may be used as an adjunct in evaluating the tumor markers in the diagnosis of EC patients. Since CRP is a sensitive, but nonspecific marker of inflammation, it might be helpful in the evaluation of EC.